Pendidikan Islam Kontemporer - Abdul Nasir (Lembaga Pengembangan Kinerja Dosen, 2025)
Contemporary Islamic education is an educational concept that integrates Islamic values ​​with technological advances and the needs of the times. This study aims to understand the concept of contemporary Islamic education and its implementation in the Islamic education system. Contemporary education seeks to integrate Islamic teachings with the current modern education system. Contemporary Islamic education has several advantages, such as the ability to integrate Islamic values ​​with technological advances and the needs of the times. However, contemporary Islamic education also has several challenges, such as the ability to face rapid changes in the times such as the development of science and technology, globalization and social change, the need for quality education, integration of Islamic values, and Islamic educational institutions that can answer the challenges of the times.